Up-regulation of endothelial nitric oxide synthase (eNOS), silent mating type information regulation 2 homologue 1 (SIRT1) and autophagy-related genes by repeated treatments with resveratrol in human umbilical vein endothelial cells. Issue 12 (11th June 2013) - Takizawa, Yoshie; Kosuge, Yukiko; Awaji, Hiroyo; Tamura, Emi; Takai, Ayako; Yanai, Takaaki; Yamamoto, Reiko; Kokame, Koichi; Miyata, Toshiyuki; Nakata, Rieko; Inoue, Hiroyasu
Abstract : Resveratrol, a polyphenolic phytoalexin found in red wine and various plants, has been reported to up-regulate the expression of endothelial NO synthase (eNOS) in human umbilical vein endothelial cells (HUVEC). However, this effect was neither long term in nature nor physiologically relevant at the concentration of resveratrol studied. In the present study, we investigated the effects of repeated treatments with a lower concentration of resveratrol on the expression of genes in HUVEC. The expression levels of eNOS and silent mating type information regulation 2 homologue 1 (SIRT1) were up-regulated in HUVEC by repeated treatments with 1 μm -resveratrol for 6 d, but not with fenofibrate. Moreover, resveratrol treatment increased the expression of autophagy-regulated genes such as γ-aminobutyric acid A receptor-associated protein ( GABARAP ), microtubule-associated protein 1 light chain 3B ( LC3B ) and autophagy-related protein 3 ( ATG3 ), the radical scavenger activity-related metallothionein-1X ( MT1X ) gene and the anti-inflammatory activity-related annexin A2 ( ANXA ) gene. In addition, resveratrol treatment down-regulated the expression of the cell-cycle checkpoint control RAD9 homologue B ( RAD9B ) gene. These results indicate the beneficial effects of resveratrol on the cardiovascular system.